Study of isotherm, thermodynamic characteristics and sorption mechanism of toluene adsorption on zeolite CsZSM-5 by adsorption-calorimetric method - Bakhronov, Khayot; Ergashev, Oybek; Оchilov, Gʻolibjon; Ganiev, Abror; Akhmedova, Nodira; Ochilova, Ozoda (Edelweiss Applied Science and Technology, 2024)
This paper presents experimental results of isotherm and basic (H, F and S) thermodynamic characteristics of toluene adsorption in CsZSM-5 zeolite. A system consisting of a universal high-vacuum adsorption unit and a Tiana-Calvet type differential microcalorimeter DAC-1-1A coupled to it was used to measure the adsorption isotherm and differential heats of adsorption, giving directly quantitative and qualitative characteristics of the nature and forces of adsorption interaction between adsorbent and adsorbate. A correlation between adsorption-energy characteristics was found and the molecular mechanism of toluene adsorption in CsZSM-5 zeolite throughout the filling region was revealed. Toluene adsorbed in CsZSM-5 zeolite is located in the first coordination sphere with Cs+ cation, forming two-dimensional complexes. It was found that the charge density of cesium cation significantly affects the molecular mechanism, adsorption energetics and the number of adsorbed toluene molecules. It was determined that the average molar entropy of toluene adsorption in CsZSM-5 zeolite is equal to -73 J/molK indicating that the mobility of toluene molecules in CsZSM-5 zeolite is lower than the liquid phase and close to the mobility of the solid phase, indicating a strong inhibition of the mobility of toluene molecules both on cesium cations and without cationic parts of the zeolite, i.e. where there are no cesium cations. This work shows how calorimetric data can be used to complement crystal structure results and to detect subtle adsorbent/adsorbate interactions at the molecular level.